Effective implementation of risk/principles based approach in a supervisory authority - Huertas, Thomas (Henry Stewart Talks, 2009)
Supervision is part of a broader tapestry, Building a consistent framework, Does monetary policy crank the asset cycle?, A troubled environment, Business models pose challenges, Senior management is responsible for assuring compliance with principles and rules, Capital and liquidity, Valuation processes require improvement, The control environment needs strengthening